Millions and millions of people pouring in: a multimodal analysis of migrants’ representation and the anti-migrant posture in Trump’s speech - Cataldo, Laure (Rzeszów University Press, 2025)
This study offers a critical and multimodal discourse analysis of Trump’s anti-immigration rhetoric during the final weeks of the 2024 U.S. presidential campaign. Drawing on a corpus of 135 annotated video clips totalling 180 minutes and primarily sourced from the X platforms TheWarRoom and The Blazen – the analysis investigates how discursive, rhetorical, and gestural strategies construct a consistent anti-migrant posture. The study reveals that Trump deploys a combination of dehumanizing metaphors, militarized language, and emotionally charged narrative elements to frame migrants as existential threats. Through repetition, hyperbole, and generalization, his discourse reinforces ideological polarization and normalizes extreme political responses. Migrants are systematically portrayed as criminals, invaders, and carriers of disease, while Trump’s use of gesture – particularly beats, deictic pointing, and eyebrow raises—further intensifies the rhetorical impact of his claims. The conflation of terms such as “asylum seekers”, “illegal immigrants”, and “criminals” adds to a climate of confusion and fear, amplified by selective references to statistical data. The study concludes that Trump’s multimodal discourse contributes not only to legitimizing harsh immigration policies but also to shaping public affect and political identity through the strategic mobilization of fear. This research thus illustrates the rhetorical power of populist discourse in constructing socially divisive narratives under the guise of national defense.
Keywords: Trump; anti-immigration stance; corpus; 2024 campaign; political speech